In the light of what we know : a novel - Rahman, Zia Haider, 1969- (Farrar, Straus and Giroux, 2014)
"A bold, epic debut novel set during the war and financial crisis that defined the beginning of our century. An investment banker approaching forty, his career collapsing and his marriage unraveling, receives a surprise visitor at his West London town house. Confronting the disheveled figure of a South Asian male carrying a backpack, the banker recognizes a long-lost college friend, a mathematics prodigy who disappeared many years earlier under mysterious circumstances. The friend has resurfaced with a confession of unsettling power. Zia Haider Rahman takes us on a journey of exhilarating scope, ranging over Kabul, London, New York, Islamabad, Oxford, Princeton, and Sylhet, and dealing with love, belonging, finance, cognitive science, and war. Its framework is an age-old story: the friendship of two men and the betrayal of one by the other, both of them desperate in their different ways to climb clear of their wrong beginnings. Set against the breaking of nations and beneath the clouds of economic recession, the novel chronicles the lives of people carrying unshakable legacies of class, culture, and faith as they struggle to tame their futures. In the Light of What We Know is by turns tender, intimate, and panoramic, telescoping the great upheavals of our young century into a first novel of rare ambition and profundity. "--